2020
DOI: 10.1139/cjpp-2019-0340
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D alleviates oxidative stress in adipose tissue and mesenteric vessels from obese patients with subclinical inflammation

Abstract: Obesity is an age-independent, lifestyle-triggered, pandemic disease associated with both endothelial and visceral adipose tissue (VAT) dysfunction leading to cardiometabolic complications mediated via increased oxidative stress and persistent chronic inflammation. The purpose of the present study was to assess the oxidative stress in VAT and vascular samples and the effect of in vitro administration of vitamin D. VAT and mesenteric artery branches were harvested during abdominal surgery performed on patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…In addition to representing the main storage site for vitamin D and expressing key enzymes involved in vitamin D metabolism, AT is also a primary target of vitamin D action, where this hormone modulates insulin-sensitivity, local inflammation, and adipokine secretion. Evidence from clinical [53] and experimental studies [54] showed that treatment with vitamin D improved AT oxidative stress [53] and local concentrations of pro-inflammatory cytokines, such as the tumor necrosis factor α TNF-α and the monocyte chemoattractant protein-1 (MCP-1) [54]. Indeed, vitamin D ameliorates AT inflammation and prevents liver steatosis by reducing both AT output of lipid droplets and hepatic de novo lipogenesis and fatty acid oxidation [55].…”
Section: Vitamin D/vdr Axis In the Pathophysiology Of Mafldmentioning
confidence: 99%
“…In addition to representing the main storage site for vitamin D and expressing key enzymes involved in vitamin D metabolism, AT is also a primary target of vitamin D action, where this hormone modulates insulin-sensitivity, local inflammation, and adipokine secretion. Evidence from clinical [53] and experimental studies [54] showed that treatment with vitamin D improved AT oxidative stress [53] and local concentrations of pro-inflammatory cytokines, such as the tumor necrosis factor α TNF-α and the monocyte chemoattractant protein-1 (MCP-1) [54]. Indeed, vitamin D ameliorates AT inflammation and prevents liver steatosis by reducing both AT output of lipid droplets and hepatic de novo lipogenesis and fatty acid oxidation [55].…”
Section: Vitamin D/vdr Axis In the Pathophysiology Of Mafldmentioning
confidence: 99%
“…In addition, a negative association between serum 25(OH)D and several biomarkers of systemic inflammation has been reported by several authors [ 23 ], regardless of the total quantity of fat mass, whereas others have showed no relationship between these parameters, which points to the lack of involvement of 25(OH)D in the pro-inflammatory milieu in obese individuals [ 24 ]. Finally, vitamin D shortage seems to be associated with depleted antioxidant status [ 25 ] and increased reactive oxygen species generation [ 26 ]. Given this gap in the understanding of the relationship between vitamin D shortage and obesity, T2DM and the underlying abnormalities, the objectives of our study were: (i) to investigate whether the degree of overweight/obesity is associated with various 25(OH)D deficiency levels; (ii) to analyze the relationship between 25(OH)D status and overweight/obesity, IR, systemic inflammation and oxidative stress; and (iii) to explore whether this putative relationship is mediated by BMI as an indicator of overweight/obesity status in a group of patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that PCOS patients have lower vitamin D status compared to healthy subjects. 8,9 Moreover, It has been suggested that vitamin D deficiency may be associated with metabolic disorders in PCOS. 10,11 The association between vitamin D levels and IR since a causative relation from a pathological point of view cannot be given due to the study design.…”
Section: Introductionmentioning
confidence: 99%